Nucleic Acid of Rubella Virus and Its Replication in Hamster Kidney Cells - Sedwick, W. David (1970)
Ribonucleic acid (RNA) has been isolated from partially purified rubella virus preparations and fractionated by rate zonal centrifugation in sucrose density gradients. The bulk of the RNA sedimented as a sharp band with a sedimentation coefficient of 38S. Rubella virus RNA appears to be single-stranded on the basis of its sensitivity to the degrading action of ribonuclease. Fractionation by precipitation with 1 m NaCl, followed by chromatography on cellulose columns, and by rate zonal centrifugation in sucrose density gradients of labeled RNA isolated from actinomycin D-treated and infected baby hamster kidney cells revealed the presence of the following virus-specific types of RNA: (i) single-stranded RNA with a heterogeneous sedimentation pattern, the 38S viral RNA becoming the predominant species only after long periods of labeling late after infection; (ii) double-stranded RNA with a sedimentation coefficient of 20S; (iii) RNA apparently composed of 20S double-stranded RNA and single-stranded branches. On the basis of their properties, the last two species were tentatively identified as the replicative form and the replicative intermediate of rubella virus RNA. Rubella virus RNA was infectious.